Quantitative study on redistribution of nitrogen and phosphorus by wetland plants under different water quality conditions. (June 2020) - Xing, Weimin; Han, Yuguo; Guo, Zifan; Zhou, Yue
Abstract: The application of wetland plants to purify surface rivers has gradually become an important means to control water pollution. However, there are many species of wetland plants which differ greatly in living conditions, water purification effects and pollutant migration paths. Therefore, it is necessary to select suitable wetland plants and quantitatively analyze the effects of different wetland plants on pollutant transport paths for the protection of water quality. In this research, the Typha orientalis C. Presl (T), Lemna minor L. (L) and Ceratophyllum demersum L. (C) were selected as typical wetland plants to conduct single-factor and multi-factor experiments under different water quality conditions. The results showed that wetland plants had significantly decreased nitrogen (N) and phosphorus (P) concentration in two sewage bodies. The NH4 + -N and NO3 − -N removal efficiencies ranged from 71 to 96% and from 46% to 76%, and the PO4 3- -P removal efficiencies ranged from 79% to 94% . The concentration of nutrient in the sewage decreased rapidly in the early stage and then tended to reach a stable state. The total nitrogen (TN) removal efficiencies under two kinds of sewage ranked as follows: T+L+C>T>C>L. Under high concentration sewage, the TN removal efficiencies by wetland plants mostly attributed to the change in the microbial status of the water body, which ranged from 82% to 95%. Under low concentration sewage, the combination of wetland plants could optimize the purification effect of plant consumption and microbial decomposition, and the TN removal efficiencies ranged from 75% to 95%. The total phosphorus (TP) removal efficiencies of T and T+L+C were better in two concentration sewages. The research demonstrated that P in sewage was mainly accumulated in soil matrix and it was important to select the emergent plants with well-develoed roots and vigorous growth to purify sewage. Graphical abstract: Image 1 Highlights: Nutrient removal efficiency and migration paths of wetland plants purify sewage were clarified. Plant consumption and microbial decomposition were two main N removal pathways. P in sewage was mainly accumulated in soil matrix. The emergent plants with well-developed roots is better to purify sewage. Abstract : The purification mechanisms of wetland plants were studied based on the analysis of nitrogen and phosphate migration paths. The principles for the application of wetland plants under different water quality conditions were proposed.